Genetic Analysis of Nucleoside Diphosphate Kinase Variants in Escherichia coli: Implications for Virulence and Inflammatory Responses (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
This manuscript explores the importance of Nucleoside Diphosphate Kinase (NDK) inside the pathogenicity of diverse microorganisms, especially focusing on Escherichia coli (UPEC), Leishmania, and Mycobacterium tuberculosis (MTB). Using in silico analyses, we visualize and evaluate NDK conformations among those species, with specific emphasis on a serine residue at function 22, highlighted for its capability role in nucleotide metabolism and virulence. Through a couple of series alignment and phylogenetic evaluation, we set up that the presence of this serine residue correlates with greater metabolic flexibility in virulent strains of E. coli  and its involvement in host interactions thru inflammatory caspases. The observe applies statistical techniques, consisting of ANOVA and the Disparity Index, to explain variations in substitution patterns and conservation of key residues, indicating evolutionary pressures favoring virulent lines. Our findings demonstrate that conserved enzymatic mechanisms throughout those pathogens should function capability objectives for therapeutic intervention. This study underscores the critical function of NDK in expertise the metabolic diversifications that underpin the virulence of those numerous organisms.